1995
DOI: 10.1016/0378-5955(95)00134-1
|View full text |Cite
|
Sign up to set email alerts
|

Auditory time-intensity cues in the binaural interaction component of the auditory evoked potentials

Abstract: Binaural interaction in the brainstem and middle latency auditory evoked potentials to intensity (dl) and timing differences (dT) between the two ears was studied in 10 normal hearing young adults. A component reflecting binaural interaction in the brainstem potentials occurred at approximately 7 ms and was of largest amplitude when d I and dT were 0. The latency of the binaural interaction component gradually shifted and its amplitude decreased as dl or dT increased and binaural interaction became undetectabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
89
6
5

Year Published

1997
1997
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(108 citation statements)
references
References 29 publications
8
89
6
5
Order By: Relevance
“…1 point into the approximate direction of the lateralization of the stimuli. Both an ITD of 0.4 ms and an ILD of 12 dB cause a strong, but not extreme lateralization of about 70³ (Furst et al, 1985;McPherson and Starr, 1995). A stronger, almost complete lateralization is produced by the synergistic stimuli L33 and R++ whose ILDs and ITDs point into the same direction.…”
Section: Stimulimentioning
confidence: 87%
See 4 more Smart Citations
“…1 point into the approximate direction of the lateralization of the stimuli. Both an ITD of 0.4 ms and an ILD of 12 dB cause a strong, but not extreme lateralization of about 70³ (Furst et al, 1985;McPherson and Starr, 1995). A stronger, almost complete lateralization is produced by the synergistic stimuli L33 and R++ whose ILDs and ITDs point into the same direction.…”
Section: Stimulimentioning
confidence: 87%
“…Brantberg et al (1999a) studied DN1 as a function of the ITD and found approximately constant amplitudes for ITDs up to 1 ms. In contrast, McPherson and Starr (1995) reported that the DN1 component gradually decreased with increasing ILD and ITD, and became undetectable for ILD s 16 dB and ITD s 1.6 ms. They stated an inverse correlation between DN1 amplitude and the psychophysical lateralization (introduced by either ILD or ITD).…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations